Analysis of the Influence of Principal Leadership on Improving Graduate Quality in Private Junior High Schools - Zaenal Abidin; Sigit Haryanto; Djalal Fuadi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The quality of graduates is a vital indicator of the success of educational institutions, especially for Private Junior High Schools (SMP) operating in a competitive environment that demands high accountability and comparative advantage. The role of School Principal Leadership is believed to be the main determining factor that mediates efforts to improve this quality. This research aims to empirically analyze and measure the influence of School Principal Leadership on the improvement of graduate quality in private SMPs, encompassing both academic and non-academic aspects. This study employed a quantitative approach with an ex-post facto survey design and sampled 30 accredited Private SMPs in the [Specify Study Area] region. Respondents consisted of 30 School Principals and 180 Teachers selected through the Simple Random Sampling technique from each sampled school. Data were collected using a Likert-scale questionnaire to measure the School Principal Leadership variable (Transformational and Instructional dimensions) and the Graduate Quality Improvement variable (teacher perception), supported by objective documentation data (exam scores and student acceptance into leading schools). Data analysis was performed using multiple linear regression tests after ensuring that the prerequisite analysis tests (Normality and Homoskedasticity) were met. School Principal Leadership, particularly through transformational practices focused on teacher motivation and empowerment, is a key determinant in achieving improved graduate quality in Private SMPs. Schools are advised to prioritize the development of transformational and instructional leadership capacity to ensure excellent graduates in both academics and character.